1983
DOI: 10.1093/infdis/147.2.318
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine for Enterotoxigenic Escherichia coli Based on Synthetic Heat-Stable Toxin Crossed-Linked to the B Subunit of Heat-Labile Toxin

Abstract: Synthetically produced Escherichia coli heat-stable toxin (ST) was conjugated to the nontoxic B subunit of the heat-labile toxin (LT) by the carbodiimide reaction. Modifying the molar ratio of toxins mixed and the ratio of carbodiimide added to the toxins permitted synthesis of conjugates with any desired degree of proportional antigenicity for each toxin component. Immunization of rats by the parenteral/peroral routes with cross-linked vaccine containing 39% ST and 61% B subunit antigenicity, with 0.06% resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…In the next step toward developing an ST vaccine, synthetic ST was conjugated to the B subunit of the heat-labile enterotoxin (LT-B) and shown to be immunogenic in both rats and rabbits. These immunized animals were protected in challenge experiments with ST and ST-producing ETEC (22,23,27). Interestingly, the chemical coupling of ST to LT-B reduced the toxicity more than 600-fold (22).…”
Section: St Vaccinologymentioning
confidence: 99%
“…In the next step toward developing an ST vaccine, synthetic ST was conjugated to the B subunit of the heat-labile enterotoxin (LT-B) and shown to be immunogenic in both rats and rabbits. These immunized animals were protected in challenge experiments with ST and ST-producing ETEC (22,23,27). Interestingly, the chemical coupling of ST to LT-B reduced the toxicity more than 600-fold (22).…”
Section: St Vaccinologymentioning
confidence: 99%
“…Because of their small size, STa enterotoxins are nonimmunogenic by themselves but can behave as haptens. Hence, a promising approach for development of immunoprophylactic agents against diarrhea caused by STa is the coupling of this protein to larger carrier molecules by chemical (5,23,24) or genetic (4,(18)(19)(20) means. We have studied the possibility of using the E. coli OmpC outer membrane protein (12) as a carrier protein for STa.…”
mentioning
confidence: 99%
“…Studies to date have demonstrated that it is possible, either by chemical conjugation of ST peptides to carrier molecules [35,36,37,38,39], or by genetic construction of ST-fusion proteins [40,41,42,43,44,45], to induce antibodies to ST. Earlier experiments with a modified ST molecule conjugated to heat-labile toxin B subunit (LT-B) provided compelling evidence that it is possible to generate neutralizing antibodies against ST in humans.…”
Section: Strategies To Neutralize Toxin Deliverymentioning
confidence: 99%